1955
DOI: 10.1002/aic.690010104
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer in packed beds

Abstract: Although considerable work has been done on the problem of heat transfer radially in fixed beds through which gases are flowing, the data available for mass transfer are limited to one pipe size and one packing size and refer to average diffusivities for the entire bed. The present study was undertaken to determine: (1) diifusivities over a range of pipe and packing sizes and (2) the effect of radial position in the bed. Empirical correlations are then presented for both point Peclet numbers, which vary wit11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
0
3

Year Published

1957
1957
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(61 citation statements)
references
References 3 publications
9
49
0
3
Order By: Relevance
“…Also shown in Dorweiler and Fahien (1959) performed similar experiments that agreed with Schwartz and Smith (1953) and went to flowrates as low as 30 cm/min. In a later study by Fahien and Smith (1955) significant radial effects were observed for column-to-particle diameters less than 20.…”
Section: Radial Flow Maldistributionmentioning
confidence: 99%
“…Also shown in Dorweiler and Fahien (1959) performed similar experiments that agreed with Schwartz and Smith (1953) and went to flowrates as low as 30 cm/min. In a later study by Fahien and Smith (1955) significant radial effects were observed for column-to-particle diameters less than 20.…”
Section: Radial Flow Maldistributionmentioning
confidence: 99%
“…10,11) The basic differential equation for mass transfer, which considers diffusion in the radial direction only and bulk flow in the axial direction, is written as Eq. (1) 6.…”
Section: Discussionmentioning
confidence: 99%
“…Fahien (6) were found to increas~ with the particle diameter to duct ~iameter ratio and to be substantially independent of mass velocity for mass velocities above 500 lbs/hr/sq ft. Air from a high pressure. source was used as the bulk stream gas.…”
Section: Literature ·Reviewmentioning
confidence: 99%
“…Under the rigid assumptions .that the mass transfer proces~ is, a function of, local flow conditions, Fahien · (6) .solved equatiqns 2 and 3 allowing both the total diffusivity, ~' arid the velocity, uz (or u), to vary with radial position. The solution is in terms of finite difference equations and may .…”
Section: Semi-numerical Solution Of Equations 2 Andmentioning
confidence: 99%